Influence of axenic culture of Bacillus clausii and mixed culture on biofilm formation, carbon steel corrosion, and methyl ester degradation in B30 storage tank system. Issue 3 (June 2022) - Aslan, Christian; Aulia, Nadia Ijkri; Devianto, Hary; Harimawan, Ardiyan
Abstract: Biodiesel (fatty acid methyl ester) from palm oil (majorly methyl palmitate and methyl oleate) is a renewable alternative energy which is used in Indonesia as a diesel blend with a composition of 30 %-v biodiesel and 70 %-v petrodiesel (B30). However, biodiesel has some disadvantages, such as more polar, easier to degrade, and hygroscopic properties, which enhance the occurrence of Microbiologically Influenced Corrosion (MIC) in diesel blend storage tank systems. In this research, the axenic culture of Bacillus clausii was studied because it was isolated and detected from the biofilm which is formed in petrodiesel solution. Moreover, the mixed culture of the biofilm was also isolated and studied in this research. These cultures are used to determine their influence on the biofilm formation, carbon steel corrosion, and methyl ester degradation in B30 storage systems. Results showed that the mixed culture enhances corrosion of carbon steel and increases the total acid number of diesel blend higher than the axenic culture of B. clausii . Results also showed that carbon steel has outstanding relative corrosion resistance because the uniform corrosion rate of carbon steel exposed at the oil phase in the B30 diesel blend storage tank is very low. However, the dangers of pitting corrosion attacks and corrosion that occurred at the oil-water interface also need to be considered. Pitting corrosion is caused by uneven biofilm, which is more dangerous because the attack is localized under biofilm and harder to detect, resulting in leakage unpredictable and reducing service tank life greater. Graphical Abstract: ga1 Highlights: Biodiesel has some disadvantages which enhance biocorrosion of carbon steel tank. TPC, gravimetry, SEM-EDX, FTIR, total acid number, and GC-MS analysis are used. Mixed culture contributes in higher corrosion rate and total acid number. Carbon steel has outstanding relative corrosion resistance to store B30 (oil phase).